Looking Beyond the Horizon: How Climate Change Impacts and Adaptation Responses Will Reshape Agriculture in Eastern Europe and Central Asia - Sutton, WilliamR. (World Bank, 2015)
Agriculture and climate change are inextricably linked, as agriculture is one of the most climate-sensitive of all sectors. In many countries, such as the four that are examined in this work, the risks of climate change for the agricultural sector are a particularly immediate and important problem because the majority of the rural population depends either directly or indirectly on agriculture for their livelihoods. The risks of climate change cannot be effectively dealt with, and the opportunities cannot be effectively exploited, without a clear plan for aligning agricultural policies with climate change, for developing key agricultural institution capabilities, and for making needed infrastructure and on-farm investments. Developing such a plan ideally involves a combination of high-quality quantitative analysis and consultation with key stakeholders, particularly farmers, as well as local agricultural experts. The most effective plans for adapting the sector to climate change will involve both human and physical capital enhancements, but many of these investments can also enhance agricultural productivity right now, under current climate conditions. The experiences of Albania, FYR Macedonia, Moldova, and Uzbekistan, highlighted in this work, show that it is possible to develop a plan to meet these objectives; one that is comprehensive, empirically-driven, and yet consultative and quick to develop. This plan also relies heavily on rigorous modeling that recognizes the importance of temperature, precipitation, and general water availability in forecasting changes to farm output and that considers multiple crop types and also livestock. This work draws on the experience of applying this approach to these four nations in Europe and Central Asia with the ultimate goal to help each country mainstream climate change adaptation into agricultural policies, programs, and investments. It also highlights the projected impacts of climate change on agriculture in these countries through forecast variations in temperature and rainfall patterns so crucial to farming, and as a result, offers a map for navigating the risks and realizing the opportunities.